2020
DOI: 10.3390/jcm9082619
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of IgA Deposition in the Kidney of Patients with IgA Nephropathy and Minimal Change Disease

Abstract: Approximately 5% of patients with IgA nephropathy (IgAN) exhibit mild mesangial lesions with acute onset nephrotic syndrome and diffuse foot process effacement representative of minimal change disease (MCD). It is not clear whether these unusual cases of IgAN with MCD (IgAN-MCD) are variant types of IgAN or coincidental deposition of IgA in patients with MCD. In a retrospective multicenter cohort study of 18 hospitals in Korea, we analyzed 46 patients with IgAN-MCD. Patients with endocapillary proliferation, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Whether MCD-IgAN is a variant form of IgAN or simply MCD superimposed on mild underlying IgAN or even with quiescent IgA deposition coincidence of MCD has not been established yet. Although several published studies have described the clinical and pathological features of MCD-IgAN and suggested it as a dual glomerulopathy ( Qin et al, 2013 ; Wang et al, 2013 ; Woo et al, 2013 ; Herlitz et al, 2014 ; Li et al, 2016 ; Cho et al, 2020 ), advanced studies on the pathogenesis of MCD-IgAN are rare. In the present study, we explored the comprehensive immune characteristics of MCD-IgAN patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether MCD-IgAN is a variant form of IgAN or simply MCD superimposed on mild underlying IgAN or even with quiescent IgA deposition coincidence of MCD has not been established yet. Although several published studies have described the clinical and pathological features of MCD-IgAN and suggested it as a dual glomerulopathy ( Qin et al, 2013 ; Wang et al, 2013 ; Woo et al, 2013 ; Herlitz et al, 2014 ; Li et al, 2016 ; Cho et al, 2020 ), advanced studies on the pathogenesis of MCD-IgAN are rare. In the present study, we explored the comprehensive immune characteristics of MCD-IgAN patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, with respect to MCD-IgAN, whether it shares the same immunopathogenesis of the four-hit processes as IgAN still needs to be investigated. Until now, only one published study from Cho et al confirmed positive Gd-IgA1 deposition in the glomeruli of IgAN-MCD patients and inferred that Gd-IgA1 played a role in the pathogenesis of MCD-IgAN and IgAN ( Cho et al, 2020 ). However, this information should be interpreted carefully.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may be a result of AP system dysregulation. Some previous studies have documented a decrease in renal function in C3G patients at diagnosis [ 20 , 21 ]. Considering these findings together with our current results, we hypothesize that a similar clinical pattern would be present as a result of AP dysregulation—that is, renal injury and inflammation would be attributed to damage caused by the already advanced CP activation as well as additional damage due to AP dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study still has some limitations: single-center enrolled Asian patients; a short follow-up period; insufficient patient cases for some subgroups of Oxford MEST-C kidney pathology classification. Additionally, a specific podocytopathic variant of IgAN or the existence of features of minimal change disease (MCD) with diffuse podocyte foot process effacement in IgAN patients were recently reported 33 , 34 , steroid therapy was indicated an appropriate therapeutic strategy in those patients, which was also recommended by the newly-released KDIGO 2021 guidelines for the management of glomerular diseases 10 , 11 . A multicenter, double-blind, broader inclusion criteria and long-term follow-up trial are needed in the future.…”
Section: Discussionmentioning
confidence: 99%